Multigenerational Households During Childhood and Trajectories of Cognitive Functioning Among U.S. Older Adults. (19th September 2020) - Lee, Haena; Ryan, Lindsay H; Ofstedal, Mary Beth; Smith, Jacqui
Abstract: Objectives: Family structure in childhood influences early brain development and cognitive performance in adulthood. Much less is known about its long-term impact on later-life cognitive functioning. We extend the two-generation family structure approach to investigate the potential contribution of living with grandparents in multigenerational households to differences in cognitive functioning at older ages. Methods: Data were drawn from 9 waves of the Health and Retirement Study (1998–2014) merged with newly collected childhood family history data. Five types of family structure were assessed: two-parent households, two-parent households with grandparents, single-parent households, single-parent households with grandparents, and grandparent-headed households. Growth curve models were used to estimate trajectories of cognitive functioning over time. Results: Childhood family structure was significantly associated with level of cognitive functioning, but not to rate of cognitive decline. Relative to those from two-parent households, individuals who grew up in multigenerational households showed higher levels of cognitive functioning, including those living with a single parent and grandparents. Those who lived with a single parent alone were the most disadvantaged. The effects of these multigenerational households persisted net of childhood and adulthood socioeconomic status and health outcomes. Discussion: Grandparent coresidence may cultivate a socially enriched home environment, providing resources and protection for early cognitive development that could persist throughout life. Multigenerational living arrangements are likely to increase as the contemporary population ages. More research needs to be done to understand the impact of these living arrangements on future generations' brain health and cognitive aging.